A novel detection method for the pathogenic Aeromonas hydrophila expressing aerA gene and/or hlyA gene based on dualplex RAA and CRISPR/Cas12a - Lin, Ziqin; Lu, Jinfang; Wu, Sihong; Lin, Xi; Zheng, Laibao; Lou, Yongliang; Xiao, Xingxing (Frontiers in Microbiology, 2022)
Aeromonas hydrophila is an emerging waterborne and foodborne pathogen with pathogenicity to humans and warm water fishes, which severely threatens human health, food safety and aquaculture. A novel method for the rapid, accurate, and sensitive detection of pathogenic A. hydrophila is still needed to reduce the impact on human health and aquaculture. In this work, we developed a rapid, accurate, sensitive, and visual detection method (dRAA-CRISPR/Cas12a), without elaborate instruments, integrating the dualplex recombinase-assisted amplification (dRAA) assay and CRISPR/Cas12a system to detect pathogenic A. hydrophila expressing aerA and/or hlyA virulence genes. The dRAA-CRISPR/Cas12a method has high sensitivity, which can rapidly detect (about 45 minutes) A. hydrophila with the limit of detection in 2 copies of genomic DNA per reaction, and has high specificity for three pathogenic A. hydrophila strains (aerA+hlyA-, aerA-hlyA+, and aerA+hlyA+). Moreover, dRAA-CRISPR/Cas12a method shows satisfactory practicability in the analysis of the spiked human blood and stool and fish samples. These results demonstrate that our developed pathogenic A. hydrophila detection method, dRAA-CRISPR/Cas12a, is a promising potential method for the early diagnosis of human A. hydrophila infection and on-site detection of A. hydrophila in food and aquaculture.